Magnetic Mechanism for the Biological Functioning of Hemoglobin - Mayda, Selma; Kandemir, Zafer; Kandemir, Zafer; Bulut, Nejat; Bulut, Nejat; Mayda, Selma; Maekawa, Sadamichi (Nature Publishing Group, 2020)
The role of magnetism in the biological functioning of hemoglobin has been debated since its discovery by Pauling and Coryell in 1936. The hemoglobin molecule contains four heme groups each having a porphyrin layer with a Fe ion at the center. Here, we present combined density-functional theory and quantum Monte Carlo calculations for an effective model of Fe in a heme cluster. In comparison with these calculations, we analyze the experimental data on human adult hemoglobin (HbA) from the magnetic susceptibility, Mossbauer and magnetic circular dichroism (MCD) measurements. In both the deoxygenated (deoxy) and the oxygenated (oxy) cases, we show that local magnetic moments develop in the porphyrin layer with antiferromagnetic coupling to the Fe moment. Our calculations reproduce the magnetic susceptibility measurements on deoxy and oxy-HbA. For deoxy-HbA, we show that the anomalous MCD signal in the UV region is an experimental evidence for the presence of antiferromagnetic Fe-porphyrin correlations. The functional properties of hemoglobin such as the binding of O-2, the Bohr effect and the cooperativity are explained based on the magnetic correlations. This analysis suggests that magnetism could be involved in the functioning of hemoglobin.